Long-Term Refractive and Topographical Changes in Keratoconic Eyes after Accelerated Corneal Crosslinking - Benca Kapitánová, Karolína; Javorka, Michal; Vida, Rastislav; Ťažandláková, Monika; Budinská, Miroslava; Kralik, Michal; Žiak, Peter; Halička, Juraj (Ceska a slovenska oftalmologie, 2025)
AIM: To evaluate the long-term impact of accelerated corneal cross-linking (A-CXL) on selected refractive and topographical parameters in eyes with progressive keratoconus. METHODS: 77 eyes with keratoconus in 54 patients treated with A-CXL (10 min "epi-off" protocol) were included in the analysis. Preoperative and postoperative (1, 3 and 5 years after A-CXL) values of the studied parameters were compared. RESULTS: In the cohort, there was an improvement in best corrected central visual acuity (BCCVA) 1 year (p = 0.004) and 3 years (p.
Keywords: Cross-Linking Reagents; progressive keratoconus; accelerated corneal cross-linking; refractive and topographical parameters; fotosenzibilizující látky; Riboflavin; Humans; Photosensitizing Agents; Female; mladý dospělý; dospělí; lidé; fotochemoterapie; kolagen; reagencia zkříženě vázaná; Collagen; Adult; ženské pohlaví; Keratoconus; Male; rohovková topografie; Corneal Topography; Adolescent; refrakce oka; Young Adult; Refraction, Ocular; Photochemotherapy; keratokonus; mužské pohlaví; Visual Acuity; zraková ostrost; riboflavin; mladiství